Introduction To Thematic Issue On Music In Asia - Paul Dale, Joshua (Penerbit Universiti Sains Malaysia (USM Press), 2013)
This issue brings together articles from diverse disciplines to examine music in Asia. Drawing upon theories and approaches in media studies, gender and fan studies, as well as anthropology, history, political science and ethnomusicology, these articles engage in a timely dialogue on how music impacts discourses of the nation state, identity formation and transnational flows of cultural production. The five articles in this volume also share surprising connections: they examine the power of music to cast an ecstatic, communal spell among youth in South Korea, as well as rural villagers in India. They trace the connections between music and politics, in Bali and the Philippines. And, they examine how music shapes identity in both diasporic communities and at home.